Global Engagement and the Occupational Structure of Firms - Carl Davidson; Fredrik Heyman; Steven Matusz; Fredrik Sjöholm; Susan Chun Zhu (Lund University, School of Economics and Management, Department of Economics, 2014)
Engagement in foreign markets can have an impact on firm organization and on the type of occupations that a firm needs. We examine the effect of globalization on the occupational mix using detailed Swedish data that cover all firms and a representative sample of the labor force for 1997-2005. We find a robust relationship between a firm's degree of international integration and its occupational mix. Multinationals, which are the most globally engaged firms, have a distribution of occupations skewed toward the more skilled. Non-multinational exporters have a distribution of occupations less skewed toward skilled compared to multinationals, but more skewed toward skilled occupations compared to Swedish non-exporters (which are the least globally engaged). Moreover, firms tend to have an even more skill intensive distribution of occupations when they mainly export to far away markets, or when they export differentiated goods. Our results are little changed (1) when we control for firm size, productivity, capital intensity, and firm age, (2) when we control for offshoring and R&D expenditures; (3) when we use alternative methods to rank occupations, or (4) when we conduct alternative robustness tests. In addition, the results are very similar for manufacturing and non-manufacturing, and for foreign and Swedish multinationals. We interpret our results using a decomposition motivated by recent theoretical models of selection into exporting and FDI.
Keywords: F14; F16; J20; 330; Occupational mix; Globalization; Multinational Enterprises; Export; Firms